Isoflavone Changes During Fermentation of Kerandang (Canavalia virosa) Milk using Lactobacillus plantarum-pentosus and its Anticancer Activity - Farianti, Djaafar Titiek; Sugahara, Takuya; Rahayu, Endang Sutriswati; Cahyanto, Muhamad Nur; Santoso, Umar; Nishi, Kosuke (Agriculture and Natural Resources, 2015)
Kerandang (Canavalia virosa) seeds contain bioactive compounds such as isoflavone whose beneficial effects need to be explored. The intake of isoflavone genistein and daidzein has been shown to provide protection against reactive oxygen species, cardiovascular disease and cancer disease among other benefits. The objective of this research was to investigate the isoflavone changes during fermentation of Kerandang milk and to evaluate its anticancer activity on colon cancer 26 cells. Kerandang milk was fermented using L. plantarum-pentosus T14 and L. plantarum-pentosus T35 for 24 hr at 37 °C. The L. plantarum-pentosus T14 and L. plantarum-pentosus T35 growth rates, total lactic acid, pH and isoflavone content were analyzed. The viability of colon cancer 26 cells was assayed using the WST-8 method. The results indicated that a change occurred from isoflavone glucoside to isoflavone aglycone during fermentation using L. plantarum-pentosus T14 and L. plantarum-pentosus T35. The methanol extract of isoflavone from Kerandang milk fermented by L. plantarum-pentosus T14 and L. plantarumpentosus T35 had anti cancer activity as indicated by the decreased viability of colon cancer 26 cells. The methanol extract of isoflavones from Kerandang milk fermented using L. plantarum-pentosus T14 has greater anti cancer activity than the methanol extract of isoflavones from Kerandang milk fermented using L. plantarum-pentosus T35 and methanol extract of Kerandang milk. In conclusion, fermentation of kerandang milk with lactic acid bacteria can increase its functional value, such as anticancer activity.